Ethnomedicinal plants with therapeutic properties - Mohan, V. R., 1959-; Doss, A., 1979-; Tresina, P. S., 1987- (Waretown, NJ : Apple Academic Press, 2019)
"Ethnomedicinal Plants with Therapeutic Properties provides detailed information on locally important medicinal plants, discusses the pharmacological properties of selected medicinal plants, and looks at the phytodrug aspects of selected plants. In 24 important chapters, the volume covers ethnomedicine, pharmacology, and pharmacognosy of selected plants Medicinal plants are an important part of our natural health. They serve as important therapeutic agents as well as valuable raw materials for manufacturing numerous traditional and modern medicines. The history of medicinal plants used for treating diseases and ailments dates back to the beginning of human civilization. Our forefathers were compelled to use any natural substance that they could find to ease their suffering caused by acute and chronic illnesses, wounds and injuries and even terminal illness. This volume highlights recent scientific evidence of therapeutic properties of traditionally used medicinal plants in relation to clinical outcomes and remedies for promotion of human well-being. The authors have endeavored to convey the therapeutic knowledge of ethnomedicinal plants clearly and concisely. This book will be helpful to undergraduate and postgraduate students, faculty, and researchers in the fields of botany, biodiversity, ethnobotany, ethnopharmacology, and others. "--
22: Evaluation of In Vivo Anticancer Activity of Ethanol Extract of Hedyotis leschenaultiana DC Against Dalton's Ascites Lymphoma-Induced Swiss Albino Mice23: In Silico Validation of Some of the Indigenous Traditional Medicines; 24: Vitexin: Phytochemical and Pharmacological Significance; Index
OCLC-licensed vendor bibliographic record.
Keywords: Materia medica, Vegetable; Medicinal plants; MEDICAL / Pharmacology